(untitled) (The Journal of Psychology and Sociology, 2016)
This paper studies the phenomenon of orphanhood, as one of the most urgent problems of social work. Оrphanhood problem always will be one of the most seri ous public unresolved problems. Graduates of orphan institution create the risk for the society, they are more prone to the offense and deviant behavior. Problems of social work with orphans in this article are considered from different sides. Different forms and types of social work with this category are explained, and its specific swere revealed. The authors explore the transfer of orphans in the respective agen cies system, allocation of financial resources at the state orphanages, determine the main advantages and disadvantages of these houses. The article puts the focus on the family upbringing of orphans and children without parental care. Today, the state is interested to build family-type orphanages and villages. The number of children brought up in familyassociatedinstitutes is considerably higher than in Government orphanages. In addition, family upbringing provides more opportunities for the suc cessful formation of the person and its further socialization. But despite these ad vantages, there aremore facts in the world practice that there is a threat of systemic violenceinfoster family for children. In this respect, the authors present their own version of improvements of the system of family upbringing of orphans and children without parental care. The article also focus on foster parenting, and on normative-legal acts regulating actions of the actors of family placement of children.